Yesterday’s Tomorrow and its Politics (KULT_online, 2022)
Futures past have been growing in popularity as a topic for historical research in recent years. The volume Politische Zukünfte im 20. Jahrhundert edited by Elke Seefried now presents an extensive overview of the interplay between futures and politics. This anthology not only compiles established findings and new insights but also points to desiderata that spark curiosity for a dynamic field of research.